Facile synthesis and fractal feature of pH-responsive poly(acrylic acid) hollow microspheres for ibuprofen delivery. Issue 15 (13th October 2018) - Wang, Qian; Jin, Xiao Qi; Sun, Ji Hong; Bai, Shi Yang; Wu, Xia; Panezai, Hamida
ABSTRACT: The pH-responsive hollow poly(acrylic acid) (HPAA) microspheres with regulated cavity structure and various shell thicknesses were synthesized. Their structural parameters and textural properties were characterized by various techniques. The ibuprofen loading results indicate the good drug loading capabilities of HPAA microspheres from 13.81 to 17.18%. Their ibuprofen release properties demonstrated their good pH sensitivity and distance-controlled drug diffusion process. Specially, the small-angle X-ray scattering technique was used to suggest the surface roughness and structural irregularities of HPAA before and after drug loading and releasing. These findings clearly indicate the potential of HPAA microspheres to be used as promising candidates in drug delivery. GRAPHICAL ABSTRACT: